Tripartite Analysis of Empowering Indicators to Student Engagement: Informing A Conceptual Framework - Li Yan; Charanjit Kaur Swaran Singh (JEELS (Journal of English Education and Linguistics Studies), 2023)
Student engagement has been labelled as the latest buzzword in the field of higher education. As it gains wide recognition as critical to learning improvement and student development, the ways contributing to engagement appear to be necessary to fully understand the definitions and potential factors. Therefore, this article employed a method of tripartite analysis to ideas on portrait engagement and comprehensively synthesized impacting variables which can empower learning engagement. Findings demonstrated an operational definition of student engagement as well as a conceptual framework illustrated in three broad factors including socio-cultural integration, structural variables and psychological dimension. The operational definition and conceptual framework provided deep insights into student engagement and implies educators systematically devise courses and teaching practices.